Evaluation of the performance of wax inhibitors on wax deposition - Liew, Shi Yan (2014)
Chemical methods were implemented in the crude oil industry to reduce wax deposition in transportation of crude oil via pipeline in subsea conditions. Poly (ethylene-co-vinyl acetate) (EVA) and diethanolamine (DEA) were used in this study to evaluate the performance as an effective wax inhibitor pair at different blend volume ratios in crude oil using cold finger method equipped with an agitator. Aside from that, the study on the rheology behaviour was carried out to validate the effects temperature and shear on the viscosity of the untreated crude oil. 10 mL volume of the wax inhibitor was injected into the cold finger equipment operating at 200 rpm, cold finger temperature at 10 ˚C, and water bath temperature surrounding the vessel at 50 ˚C. It was found that at ratio 1:1 of EVA at 400 ppm concentration to DEA was proven to be the most effective ratio blend at this operating condition with paraffinic inhibition efficiency (PIE) of 50.26%. It was also shown that EVA alone performs far better than DEA with a PIE of 17.28%. However, blend of wax inhibitors outperforms pure wax inhibitors in reducing wax deposition by a significant margin of greater PIE. The wax deposited from the inhibition of pure EVA gives a relatively hard wax texture in comparison to inhibition of pure DEA which gives a relatively softer wax texture. Wax inhibitor blends between EVA and DEA on the other hand give the softest gel texture which implicates the wax to contain lower hydrocarbons. The rheology behaviour of the crude oil behaves close to a pseudo plastic fluid where the viscosity decreases with increasing shear rate and increasing temperature. The result here will be useful to understand the effectiveness of EVA in the presence of wax dispersant, DEA to prevent severe pipeline blockage and losses of crude oil production by controlling wax deposition. It is recommended for future researches to evaluate the performance of wax inhibitor blends by varying the parameters of the cold finger equipment with respect to factors attributing to wax deposition such as molecular diffusion, shear dispersion, and effects of aging